HIGH THROUGHPUT STUDIES OF HYDROGEN EVOLUTION ELECTROCATALYST FOR WATER ELECTROLYSIS - Radwinda Kurnia Putri; Brian Hayden; Agus Prasetya; Sihana - (ASEAN Journal of Systems Engineering, 2013)
This thesis presents a study of hydrogen evolution electrocatalyst for alkaline water electrolysis. Hydrogen production through the electrolysis of water requires the development of new electrocatalysts in order to reduce the hydrogen evolution over-potential of the cathode in order to make water electrolysis more competitive and efficient. An alternative approach in the optimisation of water splitting electrocatalyst may Be the modification of the metal electrocatalytic behaviour by supporting nano-particles on oxide support. Development of the electrocatalyst material for hydrogen evolution reaction in alkaline electrolyte may obtain more stable hydrogen evolution reaction.Pt on TiO2 electrocatalyst has been synthesized by applying high throughput Physical Vapor Deposition (HT PVD) method. Electrochemistry measurements of Pt on TiO2 have been used to study the characteristic and stability of the electrocatalyst for hydrogen evolution reaction in alkaline electrolyte for water electrolysis. XRD confirmed that the phase of TiO2 were amorphous and anatase after annealing for 6 hours at the temperature of 450oC. The thicknesses of TiO2 both for amorphous and anatase were 200 nm.Similar electrocatalytic behavior are presented both for Pt on amorpous TiO2 and Pt on anatase TiO2 from electrochemistry measurements using cyclic voltammetry and potential step on the 10 x 10 E-chem arrays in alkaline electrolyte (0.5 M NaOH). Higher currents are seen in the larger particle size of platinum in TiO2 both for amorphous and anatase phase. The hydrogen evolution reaction starts at the potential below -0.8 V vs RHE. The potential for hydrogen evolution reaction is shifted to the low potential. Larger particle size of platinum shows lower potential of hydrogen evolution reaction.Pt on TiO2 tends to be a stable electrocatalyst for hydrogen evolution reaction in alkaline water electrolysis. It is because hydrogen evolution reaction occurs at low potential. Anatase phase of TiO2 is more stable than amorphous TiO2, hence, Pt on anatase TiO2 could be better than Pt on amorphous TiO2 for hydrogen evolution reaction in alkaline water electrolysis.